123k views
4 votes
I need some help please do this

1 Answer

1 vote

\begin{gathered} (-5z+6)^2-1(-5z+6)-2=0 \\ \text{Expand the perfect square:} \\ 25z^2-60z+36+5z-6-2=0 \\ \text{ Add like terms:} \\ 25z^2-55z+28=0 \\ \end{gathered}

The coefficient of z² is 25 and the constant term is 28. The product of 25 and 28 is 700. The factors of 700 which sum to -55 are -20 and -35, so:


\begin{gathered} 25z^2-55z+28=(5z-4)(5z-7) \\ so\colon \\ z=(4)/(5) \\ and \\ z=(7)/(5) \end{gathered}

User Yoel Halb
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.